2018
DOI: 10.1508/cytologia.83.155
|View full text |Cite
|
Sign up to set email alerts
|

Two Major Components of Steel Fabrication Industry, Benzene and Thinner Induce Cytotoxicity in <i>Allium cepa</i> L. Root Cells

Abstract: The various toxic chemicals used in painting of steel furniture are benzene, toluene, xylene and thinner. Of these, the cytotoxic effects of benzene and thinner were evaluated using root tip cells of Allium cepa. Chromosomal aberration assay was done and relative division rate (RDR) and mitotic index were calculated. An investigation of the root length was also carried out for 14 days in both control and after post treatment with benzene and thinner. Benzene and thinner showed positive cytotoxic effects on A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Mitotic index (MI) is an excellent parameter to understand the extent of cytotoxicity induced by any toxicant. MI using Allium cepa as test model was successfully used and reported by several workers (Barbhuiya et al, 2018;Chakraborty and Ray, 2022;Eren et al, 2015) to evaluate toxicological implication of numerous toxicants. Exposure of Allium cepa roots for 48 hours in a media containing As, signi cantly decreased the MI by approximately 5 times when compared to the CON group (6.31 ± 1.79%, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitotic index (MI) is an excellent parameter to understand the extent of cytotoxicity induced by any toxicant. MI using Allium cepa as test model was successfully used and reported by several workers (Barbhuiya et al, 2018;Chakraborty and Ray, 2022;Eren et al, 2015) to evaluate toxicological implication of numerous toxicants. Exposure of Allium cepa roots for 48 hours in a media containing As, signi cantly decreased the MI by approximately 5 times when compared to the CON group (6.31 ± 1.79%, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The toxicological implication was evaluated in the plant test system (Allium cepa) following the protocol discussed in (Barbhuiya et al, 2018) with slight modi cations. The growing roots of onion were exposed to the arsenic solution (400µg/L) and post-adsorbed solution for a period of 48 hours for the cytotoxicity study and 14 days for the phytotoxicity study.…”
Section: Root Tips Preparation and Treatment Of Allium Cepamentioning
confidence: 99%
“…The obtained results of chromosome anomalies were mostly on the same track with (Alaca et.al., 2020) after treatment the Vicia faba seeds with xylol in different concentrations (10 and 100 ml/L) for different times (12 and 24 hours) of treatment. Similarly, Barbhuiya et al (2018) investigated the effect of benzene and thinner solvents, which are used as materials in many industrial products as in the case of xylol, on the root tip cells of Allium cepa. They observed that the solvents enhanced the mitosis index and caused chromosomal anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatophyta is prominent in Cytologia, as the subject of 70 to 83% of the papers in the last two years. The subject species are very diverse, and include more detailed studies of well-known model plants such as Arabidopsis thaliana (Hayashi et al 2018b, Shibuta and Matsunaga 2019, Shimahara et al 2019, Toyoda and Matsunaga 2019 and onion, Allium cepa (Barbhuiya et al 2018, Verma and Srivastava 2018, Basu et al 2019, Roy and Roy 2019, Tütüncü et al 2019. Species with regional characteristics have also been reported, as pointed out in a Cytologia Focus two years ago (Kawano 2018).…”
Section: Cytologia Today and Microalgaementioning
confidence: 99%